2011
DOI: 10.1159/000324883
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional State Alters the Association between Free Triiodothyronine Levels and Mortality in Hemodialysis Patients

Abstract: Background: Serum free triiodothyronine (fT3) level is suggested to be a risk factor for mortality in unselected dialysis patients. We investigated the prognostic value of serum fT3 levels and also low-T3 syndrome on overall survival in a large cohort of hemodialysis (HD) patients with normal thyroid-stimulating hormone levels. Methods: A total of 669 prevalent HD patients were enrolled in the study. Serum fT3 level was measured by enzyme immune assay in frozen sera samples at the time of enrollment. Overall m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 50 publications
3
53
0
7
Order By: Relevance
“…Furthermore, Zoccali et al (14) reported that as adjustment for fT3 abrogated the association between inflammation and patient outcome, fT3 may be an intermediate pathologic indicator of systemic inflammation. In our data, as well as in Ozen et al (5), adjustment for inflammation did not affect the link between T3 and mortality. Also, associations between trimestral thyroid hormone changes and variation of inflammatory markers were somewhat weak and inconsistent in our study.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Furthermore, Zoccali et al (14) reported that as adjustment for fT3 abrogated the association between inflammation and patient outcome, fT3 may be an intermediate pathologic indicator of systemic inflammation. In our data, as well as in Ozen et al (5), adjustment for inflammation did not affect the link between T3 and mortality. Also, associations between trimestral thyroid hormone changes and variation of inflammatory markers were somewhat weak and inconsistent in our study.…”
Section: Discussionsupporting
confidence: 79%
“…Whereas earlier studies (5,14,17) only studied the association between T3 and fT3 and all-cause mortality, our study adds that this mortality prediction is mainly attributable to CV causes. The lack of mortality prediction observed by Fernández-Reyes et al (15) could relate to the selection of patients having survived at least 12 months, the low number of events encountered, and the strict inclusion criteria that excluded, among others, patients with abnormal fT3 and free T4 (fT4) levels.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations